Lao People's Democratic Republic : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Lao People's Democratic Republic. (IMF Staff Country Reports; Country Report, 2017)
This 2016 Article IV Consultation highlights that the real GDP growth of Lao People's Democratic Republic is expected to moderate from 7.5 percent in 2015 to 7 percent in 2016. Domestic activity has slowed following a less favorable external environment, and credit growth has also moderated from a high level. As growth continues to moderate in the near-term, inflation is projected to remain in low single digits. The current account deficit is projected to widen to about 19 percent of GDP in 2017 owing to the execution of large infrastructure projects with foreign direct investment.